CREATIVE STRATEGY OF BW PURBA NEGARA IN CASTING AND DIRECTING OF FIGURE MBAH SRI IN FILM “ZIARAH” - Akhlaq, Muna Rif'atil; Setiawati, Sri Wastiwi (Seni Media Rekam ISI Surakarta, 2018)
This study aims to descibe BW Purba Negara's creative strategy in casting and directing Mbah Sri character in the Ziarah film. The research method uses qualitative descriptive. The results showed, creative strategies in casting are done by going to villages looking for people who are suitable for the 3D character of Mbah Sri, based on physical suitability and the similarity of the story with the personal life of the actor Mbah Sri. In directing, creative strategies are done by reciting repeatedly and imitated, explaining explosively to be embedded in the memory of the character Mbah Sri, repeated repetition, and imitating a longdialogue.